Manipulative Figure of Kabut Asap Character in Mata Air Mata Drama Play of Lab Teater Ciputat - Pusposari, Wulan; Anoegrajekti, Novi; Attas, Siti Gomo (Universitas Negeri Medan, 2024)
The issue of manipulation in the problem of environmental damage is a topic that never expires. Literary works as a medium to disseminate good values ​​and morals in life. One of them is the drama script Mata Air Mata (MAM) by Lab Teater Ciputat which raises environmental issues. Dissemination of this good message can be done because the MAM script is a collection of collective unconsciousness that needs to be traced to the markers and signifieds of the characters it presents. This study will discuss the collective unconsciousness in the form of archetypes, semiotic archetypes, and character ideologies from an ecocritical perspective, in the MAM drama script. The limitation of the problem focuses on the dominant archetype of each character in the MAM drama script, namely the character of Kabut Asap. The research methodology uses qualitative descriptive. The discussion uses the theory of the collective unconscious of Carl Gustav Jung and the semiotics of Charles Sanders Peirce. The results of this study show that the dominant archetype of the Kabut Asap character, namely the trickster, shows the ideology of anthropocentrism.